The differences in root canal smear layer removal between 6,25% pineapple (Ananas comocus L. Merr.) peel extract and 17% Ethylene diamine tetra-acetic acid - Nirawati Pribadi; Karlina Samadi; Meliavita N. K. Astuti; Hendy J. Kurniawan; Adelina K. Tandadjaja; Ratna Puspita Hadi (Dental Journal (Majalah Kedokteran Gigi), 2019)
Background: The smear layer is attached to dentine and occludes the orifice and, consequently, must be removed in order to improve the success of inroot canal treatment. The ideal irrigation material removes both the organic and inorganic smear layers. Ethylene diamine tetra-acetic acid (EDTA) is one of the most commonly used root canal irrigation materials, but removes only inorganic smear layer. To overcome this problem, Pineapple (Ananas comosus L. Merr.) peel extract, which contains saponins, bromelain, polyphenol and flavonoid, is used during root canal irrigation. Purpose: The study aimed to analyze the difference in smear layer removal between the use of 6.25% pineapple peel extract and 17% EDTA. Methods: 27 samples of mandibular premolar teeth with straight root canals were divided randomly into three groups (n = 9) and subsequently prepared using protaper. Irrigation was performed on the control group (aquadest), group I (17% EDTA) and group II (6.25% pineapple peel extract). The samples were dried, temporarily compressed and cut horizontally from the apical to the coronal. Samples were fixed with holder before the smear layer was observed through a scanning electron microscope (SEM). The resulting data was analyzed by means of an ANOVA test. Results: The highest score of root canal hygiene was recorded by group II, followed by group I and, finally, the control group. There were significant differences between the groups (p< 0.000). Conclusion: 6.25% pineapple peel extract produces a higher smear layer removal effect than 17%EDTA on the apical 1/3 of the root canal.